Aerococcus urinae tricuspid valve infective endocarditis. Issue 4 (9th June 2022) - Banerjee, Sanchari; Murali, Sindhubarathi; Azhar, Atika; Pathmanathan, Anojan; Chaudhuri, Debanik
Abstract: Aerococcus urinae is an alpha-hemolytic, gram-positive coccus that is responsible for 54/1, 000, 000 cases of all urinary tract infections. Risk factors include male gender, advanced age, and genitourinary tract abnormalities. It has often been misidentified as Staphylococcus or Streptococcus due to its morphological similarities. Fewer than 50 cases of A. urinae infective endocarditis have been reported, most affecting the mitral or aortic valve. We present the case of a 61-year-old woman who presented with recurrent fevers and worsening dyspnea on exertion and was found to have A. urinae bacteremia. A transesophageal echocardiogram showed evidence of moderate tricuspid valve regurgitation and vegetations involving its posterior and septal leaflets. The patient was successfully treated with intravenous penicillin G for 6 weeks. She was not deemed a candidate for cardiac surgery.